Clinical Relevance of Fungi in Cystic Fibrosis - Schwarz, Carsten (Seminars in Respiratory and Critical Care Medicine, 2023)
In cystic fibrosis, a new era has started with the approval and use of highly effective cystic fibrosis transport regulator (CFTR) modulator therapy. As pulmonary function is increasing and exacerbation rate significantly decreases, the current meaning of fungal pulmonary diseases is questioned. During the past couple of decades, several studies have been conducted regarding fungal colonization and infection of the airways in people with cystic fibrosis. Although Aspergillus fumigatus for filamentous fungi and Candida albicans for yeasts remain by far the most common fungal species in patients with cystic fibrosis, the pattern of fungal species associated with cystic fibrosis has considerably diversified recently. Fungi such as Scedosporium apiospermum or Exophiala dermatitidis are recognized as pathogenic in cystic fibrosis and therefore need attention in clinical settings. In this article, current definitions are stated. Important diagnostic steps are described, and their usefulness discussed. Furthermore, clinical treatment strategies and recommendations are named and evaluated. In cystic fibrosis, fungal entities can be divided into different subgroups. Besides colonization, allergic bronchopulmonary aspergillosis, bronchitis, sensitization, pneumonia, and aspergilloma can occur as a fungal disease entity. For allergic bronchopulmonary aspergillosis, bronchitis, pneumonia, and aspergilloma, clear indications for therapy exist but this is not the case for sensitization or colonization. Different pulmonary fungal disease entities in people with cystic fibrosis will continue to occur also in an era of highly effective CFTR modulator therapy. Whether the percentage will decrease or not will be the task of future evaluations in studies and registry analysis. Using the established definition for different categories of fungal diseases is recommended and should be taken into account if patients are deteriorating without responding to antibiotic treatment. Drug–drug interactions, in particular when using azoles, should be recognized and therapies need to be adjusted accordingly.
Keywords: cystic fibrosis transport regulator; fungal colonization; cystic fibrosis